Tunisia Infrastructure Diagnostic - World Bank Group (World Bank, Washington, DC, 2021)
Tunisia’s has made significant investments in infrastructure, which has contributed to economic growth. The investments have enabled reasonably good access to basic infrastructure services. While access rates are high, the relative quality of Tunisia’s infrastructure has deteriorated significantly over the last ten years. State-owned enterprises (SOEs), which dominate the infrastructure sector, receive considerable subsidies and incur notable financial losses. Overall, there is a heavy reliance on external borrowing to fund infrastructure investment, which creates contingent liabilities, and enhances foreign exchange and macro-economic risk. Chapter one provides an overview of Tunisia’s infrastructure performance; chapter two discusses each sub-sector in more detail in terms of achievements and challenges; chapter three looks at historical trends in spending followed by a scenario analysis of investment needs with anecdotal examples, and discusses the present macro-economic and fiscal constraints; and chapter four presents possible action items for further discussion with the Tunisian government.